Indication that the Nitrogen Source Influences Both Amount and Size of Exopolysaccharides Produced by Streptococcus thermophilus LY03 and Modelling of the Bacterial Growth and Exopolysaccharide Production in a Complex Medium - Degeest, Bart (American Society for Microbiology, 1999)
Streptococcus thermophilus LY03 is a yogurt strain producing the same exopolysaccharide material in both milk and MRS broth. Actually, two types of exopolysaccharides are produced simultaneously. The two exopolysaccharides are identical in monomer composition (galactose and glucose in a 4:1 ratio) but differ in molecular size. Gel permeation chromatography revealed a high-molecular-mass exopolysaccharide (1.8 × 10(6)) and a low-molecular-mass exopolysaccharide (4.1 × 10(5)). Both exopolysaccharides can be isolated from the fermentation broth separately. The proportion in which they are produced is strongly dependent on the carbon/nitrogen ratio of the fermentation broth. A shift from a high-molecular-mass exopolysaccharide to a low-molecular-mass exopolysaccharide was observed with increasing initial complex nitrogen concentrations. All necessary biokinetic parameters to study the kinetics of S. thermophilus LY03 fermentations were obtained from a mathematical model which describes both S. thermophilus LY03 growth and exopolysaccharide production and degradation. The model is valid with various initial complex nitrogen concentrations and can be applied to simulate exopolysaccharide production in a milk medium.